(untitled) (Iraqi Journal of Medical Sciences, 2019)
Background: Circumventricular organs (CVOs) are specialized structures border the brain ventricles and lack the blood-brain barrier. These CVOs are lined by specialized ependymal cells (ECs) called tanycyte. The sulcus medianus organum (SMO) locates at the floor of the 4th ventricle at the rostral part of the sulcus medianus (SM). Objective: To explore the expression of the monocarboxylate transporter 1 and monocarboxylate transporter 4 (MCT1 & MCT4) in the tanycytes of the median eminence (ME) and tanycyte-like cells of the SMO to add a functional evidence for describing the SMO as another CVOs and to start a roadmap for the citing the SMO specifically as a sensory or a secretory CVO. Methods: Ten adult male rats (Rattus norvegicus albinus), aged 3-6 months with 300±50 g, were used to study the histological characteristics of ECs in ME and SMO with Hematoxylin & Eosin and to explore the immunohistochemical expression of MCT1 & MCT4 in ME and SMO. Results: The ependymal cells were arranged in in 2-3 layers in the depth of SMO region and single layer in the ME region as seen with H&E stains. Immunohistochemical expression of MCT1 & MCT4 using Aperioscope image analysis in tanycytes of the ME is higher than that in tanycyte-like cells of the SMO with significant differences between the two regions as proved by t-test. Conclusion: the SMO has different structural and functional properties compared to ME suggesting that the SMO may be a sensory CVO. Keywords: Circumventricular organs, tanycytes, sulcus medianus organum, median eminence Citation: Jawad HF, Al-Kaabi MA, Al-Salihi AR. Immunohistochemical expression of monocarboxylate transporter 1&4 in tanycyte–like cells of the sulcus medianus organum. Iraqi JMS. 2019; 17(1): 83-99. doi: 10.22578/IJMS.17.1.12